Validation of remote child weight and height measurements within a weight management trial - Button, Alyssa M.; Staiano, Amanda E.; Beyl, Robbie A.; Stein, Richard I.; Newton, Robert L.; Baker, Alison; Lima, Angela; Lindros, Jeanne; Conn, Anne‐Marie; Welch, R. Robinson; Cook, Stephen R.; Wilfley, Denise E. (Obesity (Silver Spring, Md.), 2024)
Objective The aim of this substudy within the Treatment Efforts Addressing Child Weight Management by Unifying Patients, Parents, and Providers (TEAM UP) pragmatic clinical trial was to compare the validity of anthropometric measurements collected remotely versus in person (≤7 days apart) among youth with obesity who were 6 to 15 years of age. Methods Child (n = 37) weight and height were measured in person by a trained data assessor. These were compared with measurements taken remotely by the child's parent with live videoconferencing observation by a study data assessor. In‐person and remote measurements were compared using Bland–Altman plots, Pearson correlations, and two one‐sided paired t tests. A priori bounds of acceptability were set at ±0.68 kg to allow for typical weight fluctuations within the 7‐day comparison period. Results Measurements were highly correlated (height: r = 0.991, p < 0.0001; weight: r = 0.999; p = 0.03). For height, two one‐sided t tests for upper, t(36) = 3.95, and lower, t(36) = −2.63, bounds (−1, 1) revealed an overall p = 0.006; absolute error was 3.5 cm. For weight, two one‐sided t tests for upper, t(36) = 1.93, and lower, t(36) = −7.91, bounds (−0.68, 0.68) revealed an overall p = 0.03; absolute error was 1.7 kg. Conclusions The present findings support the utility and interpretation of remotely assessed weight management outcomes for both research and clinical purposes. These procedures may offer greater accessibility to evidence‐based measurement.